Adaptasi Dan Transformasi Partai Golkar Di Sumatera Barat Era Reformasi Tahun 1998-2014 - Satria Okatavianus; Erniwati Erniwati; Hendra Naldi (Jurnal Kronologi, 2019)
This study describes the adaptation and transformation of postreform golkar in WestSumatera. Whether the Golkar made a change ? And Whether these post reformchange affect the existence of the Golkar Party in West Sumater a. The Purpose of thisreseach are : 1). Explaining How the Golkar Party doing Adaptation andTransformastion in West Sumatera for Reformation Era. 1). Expalaining the step ofThe Golkar Party still Exist in West Sumatera from 1998 2014. This reseach follo wingthe rules of Historical reseach that arrange on four stages, Including Heuristich,Source Critism, Interpretation, and Hsitoriograpy. Based on the result of the reseachit could be counlude that The Golkar Party of West Sumatera was overhouled theorg anization structure and turned in to Golkar Party, Consolidated, Sosialized,Registering the best people for every election period. From and stengthen AMPG andKPPG, Establish good relation with the society, give some programs that needed forpeople, carry out the Karakterdes( Kader Penggerak Desa ) and Karsinal ( KaderPenggerak Fungsional ). Evan so, in 2014 period The Golkar Party was not maximalon doing party regeneration and The Golkar Party was not Worked.